1988
DOI: 10.1007/bf00264764
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and non-oxidative glucose metabolism in non-obese Type 2 (non-insulin-dependent) diabetic patients

Abstract: Insulin resistance is a common feature of Type 2 (non-insulin-dependent) diabetes mellitus. This defect in insulin-mediated glucose metabolism could result from a defect in either glucose oxidation or non-oxidative glucose disposal. To examine this question, euglycaemic insulin clamp studies were performed in 16 normal weight Type 2 and 11 age-matched control subjects. In Type 2 diabetic patients the fasting plasma glucose concentration, 8.39 +/- 0.50 mmol/l, was allowed to decline (over 54 +/- 6 min) to 5.33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…Impaired fat oxidation was not responsible for the defect in glucose oxidation since rates of fat oxidation were identical in the NIDDM and control subjects under both basal and stimulated rates of glucose uptake. The similarity in fat oxidation rates and free fatty acid levels in control and NIDDM subjects despite reduced rates ofglucose oxidation in the NIDDM subjects in our study is supported by the findings of a number of researchers who have shown that fat metabolism in non-obese NIDDM subjects is normal despite impaired insulin-mediated glucose utilization (3)(4)(5)(45)(46)(47). Therefore, in nonobese NIDDM subjects, the defect in glucose oxidation is not associated with increased fat oxidation.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Impaired fat oxidation was not responsible for the defect in glucose oxidation since rates of fat oxidation were identical in the NIDDM and control subjects under both basal and stimulated rates of glucose uptake. The similarity in fat oxidation rates and free fatty acid levels in control and NIDDM subjects despite reduced rates ofglucose oxidation in the NIDDM subjects in our study is supported by the findings of a number of researchers who have shown that fat metabolism in non-obese NIDDM subjects is normal despite impaired insulin-mediated glucose utilization (3)(4)(5)(45)(46)(47). Therefore, in nonobese NIDDM subjects, the defect in glucose oxidation is not associated with increased fat oxidation.…”
supporting
confidence: 87%
“…Many studies have shown that rates of intracellular glucose metabolism are lower in NIDDM subjects than nondiabetic subjects (2,3,5,6). However, reduced rates of glucose oxidation and nonoxidative glucose metabolism in these studies have always been accompanied by reduced rates of glucose uptake, therefore making it impossible to determine whether these reduced rates of glucose metabolism are due to intracellular defects or simply a result of less glucose entering the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemic or euglycemic insulin clamp techniques have been used to investigate total body glucose uptake and oxidation, and glucose metabolism in skeletal muscle and other organ systems in healthy human subjects (1)(2)(3)(4)(5)(6). However, little is known about the effects of hyperglycemia on glucose utilization in the hearts of intact animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Most attention has been given to the effects of insulin resistance on glycogen storage in tissues such as skeletal muscle, but glycolytic disposal of glucose shares the steps of glucose transport and phosphorylation, which are likely to play key roles in insulin sensitivity (24), and glycolytic enzymes are sensitive to insulin. Moreover, at serum insulin concentrations in the "dynamic range" between basal and maximal (i.e., between ϳ100 and 1000 pmol/l), glycolytic disposal of glucose closely parallels glycogen storage in clamp studies and is impaired to a similar extent by insulin resistance (25,26). Measurement of glycolysis has a major advantage over glycogen synthesis, however, because tissue glycogen is not readily accessible to sampling, whereas an immediate product of glycolysis (hydrogen atoms released to tissue water) can be tagged, traced, and sampled in body fluids.…”
mentioning
confidence: 99%